2023
DOI: 10.3390/antiox12061233
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Alcohol Consumption and Oral Microbiota on Upper Aerodigestive Tract Carcinomas: A Pilot Study

Abstract: Alcohol consumption is associated with oxidative stress and an increased risk of carcinoma of the upper aero-digestive tract (UADT). Recently, it has been found that some microorganisms in the human oral cavity may locally metabolize ethanol, forming acetaldehyde, a carcinogenic metabolite of alcohol. In a cohort of patients first visited for UADT cancers, we estimated their alcohol consumption by measuring Ethyl Glucuronide/EtG (a long-lasting metabolite of ethanol) in the hair and carbohydrate-deficient tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Acetaldehyde, an aroma compound primarily derived from ethanol, has been associated with the oral microbiota's role in aromatic compound production and metabolism. Research has shown that bacteria Neisseria subflava, Streptococcus mitis, Candida albicans , and C. glabrata in the human oral cavity exhibit high alcohol dehydrogenase activity, converting ethanol to acetaldehyde (Fiore et al., 2023). Human aldehyde dehydrogenases have recently been discovered to metabolize odorant aldehydes.…”
Section: The Role Of the Oral Microbiota In Aroma Release And Perceptionmentioning
confidence: 99%
“…Acetaldehyde, an aroma compound primarily derived from ethanol, has been associated with the oral microbiota's role in aromatic compound production and metabolism. Research has shown that bacteria Neisseria subflava, Streptococcus mitis, Candida albicans , and C. glabrata in the human oral cavity exhibit high alcohol dehydrogenase activity, converting ethanol to acetaldehyde (Fiore et al., 2023). Human aldehyde dehydrogenases have recently been discovered to metabolize odorant aldehydes.…”
Section: The Role Of the Oral Microbiota In Aroma Release And Perceptionmentioning
confidence: 99%
“…Similarly, E. coli carrying the pks‐island‐produced colibactin also induced a novel mutational signature in oral squamous cell carcinoma and in other mucosal tumor types 69 . Furthermore, in oral and even upper aerodigestive tract carcinomas, the residing of certain bacteria, including Neisseria subflava , Streptococcus mitis , Candida albicans , Glabrata , etc., that are generally non‐pathogenic, could convert alcohol into carcinogen acetaldehyde and thus play a subtle role in alcohol‐related carcinogenesis in human oral cancer 70,71 . Acetaldehyde causes DNA damage and blocks DNA repair, and is usually further metabolized by aldehyde dehydrogenase (ALDH) in the liver, while in the oral cavity, the activity of ALDH is relatively low, resulting in the long existence of acetaldehyde and more deteriorating results 72,73 .…”
Section: Mechanisms Of Intratumor Microbiome In Modulating Tumor Init...mentioning
confidence: 99%